Social representations of odors: case study in the Ñuble region, Chile (2019–2023) - Parada-Ulloa, Marcos; Bozo Marambio, Jorge; Moreno-Leiva, Germán; Vásquez-Burgos, Karina; Vega Gutiérrez, Oscar; Mansilla-Sepúlveda, Juan; Larez-Hernández, José; Salazar Cayuleo, Héctor; Morales Ojeda, Ismael (Frontiers in Social Psychology, 2024)
Introduction The objective of this article is to analyze the social representation of odors and the identity of the population in the Ñuble region between 2019 and 2023. The research focuses on how industrialization and urban and rural development have altered the olfactory landscape of this region. This study seeks to understand how changes in the physical environment affect the representation of odors and how these, in turn, impact the daily lives of residents. The importance of smells is highlighted not only as sensory experiences, but also as social phenomena that influence the perception of the environment and community relationships. Methods The research adopts an interpretive approach, combining case studies and analysis of primary sources. The analysis is categorized into two main areas: public policy on odors and the situation of odors in the cities of Chillán Viejo and Chillán. Primary sources include government documents, technical reports, and interviews with residents and local authorities. The interpretive approach allows us to explore the perceptions and subjective experiences of odors among the residents of Ñuble. Results The study reveals that industrialization and urban and rural development have significantly transformed the olfactory landscape of the Ñuble region. In Chillán Viejo and Chillán, residents report changes in odors due to industrial expansion and urbanization. Public odor policy has attempted to mitigate negative impacts, but results have been mixed. While some measures have improved air quality, others have been insufficient to address community concerns. Discussion and conclusion Smells in Ñuble are not merely sensory experiences, but social phenomena that deeply affect the daily lives of residents. The perception of smells is closely linked to the identity and history of the region. Changes in the olfactory landscape have generated both adaptations and resistance among inhabitants. Public policies must consider not only the technical aspects of air quality, but also the social and cultural dimensions of odors. This study highlights the need to address odors as an integral part of urban planning and environmental policy to improve the quality of life of residents in Ñuble.